Exploring the Mental Dynamics of Incarcerated Pathological Gamblers: A Case Study in Balai Pemasyarakatan (Correctional Center) Class II Kediri - Rois Fadilah; Qurrota A’yuni Fitriana (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Impulse control disorders take various forms, one of which is pathological gambling, characterized by an individual's inability to control the urge to gamble, even though the individual knows that his actions can have negative impact. Individuals with gamblimg disorder will feel anxious and worry when not gambling and feel relieved after doing so. Correctional center, such as the Balai Pemasyarakatan, provide guidance, rehabilitation, and a sense of security for clients with psychological issues, helping them achieve recovery. This study used a qualitative method with a case study approach. Data were collected through interviews, observations, and document analysis conducted at Balai Pemasyarakatan Class II Kediri. The subject of the study was an individual with pathological gambling behavior. The findings revealed that the client had been addicted to gambling since adolescence, experienced anxiety and tension when not gambling, and spent almost all of his financial resources on gambling. His inability to control gambling urges led to involvement in theft on three occasions. However, his psychological condition improved through a series of psychological guidance and rehabilitation programs provided by the correctional center. These results indicate that comprehensive psychological assessment can have a positive impact and help prevent recidivism caused by pathological gambling.